Relationship between Alcohol Consumption and Ocular Pressure according to Facial Flushing in Korean Men with Obesity - Lee, Sami (Korean J Fam Med, 2019)
BACKGROUND: This study aimed to examine the relationship between alcohol consumption and intraocular pressure (IOP) according to facial flushing in Korean men with obesity. METHODS: The study included 479 Korean men with a body mass index of ≥25 kg/m(2) (75 non-drinkers, 174 with drinking-related facial flushing, and 230 without facial flushing) who underwent health check-ups between October 1, 2016 and March 31, 2017. Multivariate logistic regression was used to assess the relationship between alcohol consumption and high IOP (≥21 mm Hg). RESULTS: Flushers consuming ≤16 drinks per week had a significantly higher risk of high IOP than non-drinkers, depending on alcohol consumption (≤8 standard drinks: odds ratio [OR], 4.49; 95% confidence interval [CI], 1.05– 19.25; >8 but ≤16 standard drinks: OR, 8.14; 95% CI, 1.37–48.45). However, when the consumption was >16 drinks per week, the high IOP risk did not significantly increase (OR, 0.71; 95% CI, 0.05–10.69). In addition, there was no significant relationship between alcohol consumption and high IOP among non-flushers consuming ≤8 drinks per week (OR, 2.07; 95% CI, 0.52–8.19). However, a significantly increased risk of high IOP was observed among non-flushers consuming >8 drinks per week, depending on alcohol consumption (>8 but ≤16 standard drinks: OR, 4.84; 95% CI, 1.14–20.61; >16 standard drinks: OR, 4.08; 95% CI, 1.02–16.26). CONCLUSION: This study suggests that obese men with alcohol flush reactions may have an increased risk of high IOP with the consumption of smaller amounts of alcohol than non-flushers.